Effects of thickness on optical characteristics and strain distribution of thin-film GaN light-emitting diodes transferred to Si substrates. (3rd March 2016) - Li, Heng; Shi, Yang-Da; Feng, Meixin; Sun, Qian; Lu, Tien-Chang
Abstract: We investigated the effect of device thickness on the internal quantum efficiency (IQE) of thin-film GaN light-emitting diodes (LEDs), which were grown on Si substrates and transferred to other Si substrates with reduced film thickness. It was confirmed by Raman spectroscopy and photoluminescence measurement that the compressive strain is released and the quantum-confined Stark effect (QCSE) is suppressed after reducing the thickness. The best IQE of 62.9% was reached with a large suppression of the band tilting by QCSE, from 7.9 meV in the original structure to 2.4 meV in the thinnest sample, and this value can compete with that of GaN-based LEDs grown on a sapphire substrate.